KNOWLEDGE, ATTITUDES AND PRACTICES REGARDING ANALGESIC DRUG USE IN OUTPATIENTS IN TRA VINH UNIVERSITY, VINH LONG PROVINCE: A CROSS SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Background: Chronic musculoskeletal disorders are common causes of long-term pain and impaired quality of life. Analgesic drugs are frequently used in outpatient settings, and safe use requires adequate knowledge, attitudes, and practices.Objective: To describe the knowledge, attitudes, and practices regarding analgesic drug use among outpatients with chronic musculoskeletal pain.Methods: A cross-sectional study was conducted among 355 outpatients at Tra Vinh University Hospital, Vinh Long Province, Vietnam, in 2024. Data were collected via face-to-face interviews using a structured knowledge, attitudes, and practices questionnaire. Descriptive statistical analysis was performed to analyze the data.Results: The majority of participants were female. Moderate and severe pain accounted for 51.5% and 31.9%, respectively. Good knowledge, positive attitudes and good practices were observed in 34.1%, 88.0% and 56.3% of participants. Knowledge was higher for dosing and administration, whereas safety related knowledge regarding hepatic, renal and cardiovascular adverse effects was limited. Most participants obtained analgesics from healthcare facilities, though some reported self purchasing and discontinuing medications once symptoms improved.Conclusion: Participants exhibited positive attitudes and acceptable practices toward analgesic drug use; however, safety related knowledge was insufficient. Enhancing patient counseling and health education may improve safe and rational analgesic use in outpatient settings.
Keywords: Analgesics; Outpatients; Knowledge, Attitudes, Practice; Musculoskeletal Pain.